Formulation effect study on batter and cake microstructure: Correlation with rheology and texture. (July 2015) - Hesso, Nesrin; Garnier, Catherine; Loisel, Catherine; Chevallier, Sylvie; Bouchet, Brigitte; Le-Bail, Alain
Graphical abstract: Highlights: Cake structure made of swollen starch granules surrounded by proteins in a lipid phase. Weak viscoelastic properties by oil addition was related to a discontinuous batter structure. Pregelatinized starch addition led to an increase in the surface ratio of the lipid fraction in cakes. The differences in viscoelastic and textural properties of cake could be explained by their microstructure. Abstract: Changes in the mechanical and micro-structural properties of cake batter as a function of formulation impact are described. Mechanical properties were investigated by batter rheology and cake texture. Confocal laser scanning microscope (CLSM), together with image analysis technique, was used to obtain the microstructure of batters and cakes. Results showed an increase in rheological moduli values with the addition of pregelatinized starch in the batter, while fat replacement by rapeseed oil decreased the moduli values of the batter. These changes in batter visco-elastic properties resulted in different cake structures. A significant increase in the surface area of the lipid domain has been observed on CLSM images for cakes using pregelatinized starches. This was explained by the fact that part or all of the pregelatinized starch was embedded in the lipid domain for these formulations. This fact may explain the expected softer texture of the cake using such starches. CLSM in combination with image processing has been proved as an applicable tool for examining and quantifying the fat and protein microstructure in batter and cake. Hence, it was possible to prove the dependency of the texture on the microstructure of the batter and the baked "cake".